Refleksi Kerja Sama Amerika Serikat-ASEAN Di Masa Kepemerintahan Presiden Donald Trump dalam Menanggulangi Pandemi COVID-19 - Muhammad Iqbal Yunazwardi (Faculty of Social, Politic, and Law Science, Universitas Serang Raya, 2025)
The COVID-19 pandemic has urged all countries to work optimally to minimize the resulting negative impacts. Cooperation is an unavoidable effort to create maximum efforts in handling COVID-19 because no single country can solve the COVID-19 problem independently. This paper discusses how to reflect on the cooperation carried out by the United States (US) and ASEAN to solve the COVID-19 pandemic. As a major power, the US has always played an essential role in global interactions, especially in times of crisis. However, under the Trump administration, bilateral and multilateral approaches to cooperation will face challenges. As an anti-globalist, Trump will try his best to calculate the benefits that the US gets in every form of cooperation. By using a transactional bilateralism approach, this paper explains how the motive for cooperation can occur in terms of US domestic factors in handling COVID-19, the Trump administration's rational calculations, to the strategic opportunities that the US can capitalize on its cooperation with ASEAN to resolve the problem.